An Own-Age Bias in Recognizing Faces with Horizontal Information - Schaich, Andreas; Obermeyer, Sven; Kolling, Thorsten; Knopf, Monika (Frontiers in Aging Neuroscience, 2016)
Horizontal information, as a result of a selective filtering process, are essential in younger adults’ (YA) ability to recognize human faces. Obermeyer, Kolling, Schaich, and Knopf (2012) recently reported impaired recognition of faces with horizontal information in older adults (OA) suggesting age-variant processing. Two yet unconsidered factors (stimulus age and exposure duration) that may have influenced previous results, were investigated in this study. Forty-seven YA (18-35yrs) and 49 OA (62-83yrs) were tested in a 2x2x2x2 mixed design with the between-subjects factors age group (YA vs OA) and stimulus age (young faces vs older faces) and the within-subjects factors filter (filtered (HF) faces vs unfiltered faces (UF)) and exposure duration (0.8s vs 8s). Subjects were presented morph videos between pairs of faces: A starting face gradually merged into either the previously encoded target face or a control face. As expected, results showed an increase in recognition sensitivity (d’) with longer exposure duration in YA with both younger and older HF faces. OA however were unable to recognize filtered young faces not even with increased exposure duration. Furthermore, only elderly participants showed more accurate recognition with faces of their own age relative to other-age faces (own-age bias, OAB). For YA no OAB was observed. Filtered face recognition was significantly correlated with unfiltered recognition in YA but not in OA. It is concluded, that processing of horizontal information changes at a higher age. Presenting filtered or unfiltered faces both targets convergent face-specific processing only in YA but not in OA.